Indispensable biomolecules for plant defense against pathogens: NBS-LRR and “nitrogen pool” alkaloids - Liu, Qian; Zhang, Chunhong; Fang, Huiyong; Yi, Letai; Li, Minhui (Plant science (Limerick), 2023)
In a complex natural environment, plants have evolved intricate and subtle defense response regulatory mechanisms for survival. Plant specific defenses, including the disease resistance protein nucleotide-binding site leucine-rich repeat (NBS-LRR) protein and metabolite derived alkaloids, are key components of these complex mechanisms. The NBS-LRR protein can specifically recognize the invasion of pathogenic microorganisms to trigger the immune response mechanism. Alkaloids, synthesized from amino acids or their derivatives, can also inhibit pathogens. This study reviews NBS-LRR protein activation, recognition, and downstream signal transduction in plant protection, as well as the synthetic signaling pathways and regulatory defense mechanisms associated with alkaloids. In addition, we clarify the basic regulation mechanism and summarize their current applications and the development of future applications in biotechnology for these plant defense molecules. Studies on the NBS-LRR protein and alkaloid plant disease resistance molecules may provide a theoretical foundation for the cultivation of disease resistant crops and the development of botanical pesticides. [Display omitted] •Plant specific defenses include the disease resistance protein nucleotide-binding site leucine-rich repeat (NBS-LRR) protein and metabolite derived alkaloids.•The NBS-LRR protein can specifically recognize the invasion of pathogenic microorganisms to trigger the immune response mechanism.•Many defensive alkaloids are used as the main components of botanical pesticides; however, a systematic summary of the role of alkaloids as plant pathogen defense metabolites is lacking.•In this review, we examine the recognition and function of NBS-LRR proteins in plant defense, the synthesis and defense mechanisms of alkaloids, and their application in modern biotechnology.•In addition, we discuss their future development and contribution to protecting plants from pathogens.